BOLALIKTEPA IS A PEASANT SETTLEMENT BELONGING TO THE EARLY MIDDLE AGES (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
There are many ancient and pilgrimage places in the Republic of Uzbekistan. The artifacts in them will not leave anyone indifferent. In the historical complexes of our country there are such items that speak of history and the past. The more we write about the ancient residences, monuments and sites that echo from Mozi, the less we can write about them.